Aktivitas Intervensi Terapi Butterfly Hug untuk Menjaga Kestabilan Emosi terhadap Mahasiswa Baru yang Mengalami Kecemasan - Talsi, Nadhila Putri; Rahmi, Tuti (TSAQOFAH, 2026)
New university students often face adaptation challenges to the higher education environment that can trigger anxiety, which, if not properly managed, may disrupt emotional stability and the learning process. This study aimed to determine the effectiveness of Butterfly Hug therapy in maintaining emotional stability among new students experiencing anxiety. The research employed a quantitative experimental method with a one-group pretest–posttest design. The sample consisted of five first-year students of Universitas Negeri Padang, cohort 2025, selected using purposive sampling. Data were collected using an anxiety scale based on the Zung Self-Rating Anxiety Scale (ZSAS) and analyzed using a paired-samples t-test. The results showed a significance value of 0.023 (< 0.05), indicating a significant difference between anxiety scores before and after the intervention. These findings demonstrate that Butterfly Hug therapy is effective in reducing anxiety levels and maintaining emotional stability among new university students, and thus has the potential to be used as a supportive psychological intervention within student counseling services in higher education institutions.